Utilização de realidade aumentada para montagens de estruturas metálicas: uma aplicação na indústria aeronáutica - Cardoso, Luis Fernando De Souza [UNIFESP] (2019)
Among the main manufacturing challenges during the fourth industrial revolution is the quality with which product development information reaches the assembly line. One of the most studied information visualization technologies is the Augmented Reality which, nowadays, has been promoted by its use in mobile devices. However, the industrial sector still has doubts about the technology maturity and cost to attend production processes, making it scarce in the production environment. In this context, the present paper develops an Augmented Reality application that could attend aeronautical industries’ requirements for structural assemblies, analyze statistically it use compared to traditional assembly methods and identify the technology main benefits and limitations to this applicability. To perform this analysis, this study conducted a field evaluation with users who used AR to mark small brackets position in an aeronautical structure. After collecting the time and measurement to positioning the brackets, a statistical analysis was performed to compare the positioning method with AR with a traditional method using metric scale. In the end, this study points out that for higher complexity assemblies AR can offer a faster solution, even though some limitations concerning the positioning tolerance using the technology. As future work, some application modifications are suggested to reduce markup errors and overall usage time.